Petar Stambolić (1913-2007) – a short biography (Heritage, 2024)
The article outlines the biography of Petar Stambolić, a communist, revolutionary, and high-ranking party and state official during Communist Yugoslavia. Stambolić, originally from Brezova near Ivanjica, became associated with the advanced student movement in Belgrade while still a student. He joined the banned Communist Party of Yugoslavia (KPJ) in 1935 and rose through the hierarchy of the Provincial Committee, emerging as one of the prominent Serbian communists.          His political breakthrough occurred after 1948 when he was elected Secretary of the Central Committee of the Communist Party of Serbia and the Prime Minister of Serbia. In 1957, he transitioned to federal functions, initially serving as the President of the Federal People's Assembly from 1957 to 1963, and later as the President of the Federal Executive Council from 1963 to 1967. The peak of his career came after the fall of Aleksandar Ranković, where Stambolić played an active role in the preparations for Ranković's displacement. Consequently, Stambolić became the de facto most influential party official from Serbia.          He retained key roles at the federal level, contributing to the presidencies of the League of Communists of Yugoslavia and the Socialist Federal Republic (SFR) of Yugoslavia. Stambolić retired in 1984 and lived quietly in Belgrade until his death in 2007.
Keywords: Petar Stambolić, SFRY (Socialist Federal Republic of Yugoslavia), League of Communists of Yugoslavia, League of Communists of Serbia